2019
DOI: 10.1111/dmcn.14413
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life, pain, and fatigue in young adults with cerebral palsy

Abstract: Aim To describe health‐related quality of life (HRQoL), pain, fatigue, and other health variables in young adults with cerebral palsy (CP), and to explore associations with the Gross Motor Function Classification System – Expanded and Revised (GMFCS‐ER) and physical activity. Method This was a cross‐sectional study of 61 young adults at a mean age of 21 years 2 months (standard deviation 8mo, range 20–22y) with CP, from a geographically defined area. Data collection included: Short Form 36 version 2 for HRQoL,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 26 publications
3
35
0
Order By: Relevance
“…In fact, two out of three adults in this study reported pain, and of those, one in four reported severe pain. The prevalence of pain in this study is similar to previous findings of pain in adults with CP in Sweden, 28 but higher than recently reported rates for younger adults in their early twenties in Sweden (49%) 3 . This supports the notion that the frequency of pain increases rapidly during early adulthood and younger middle age in this population.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In fact, two out of three adults in this study reported pain, and of those, one in four reported severe pain. The prevalence of pain in this study is similar to previous findings of pain in adults with CP in Sweden, 28 but higher than recently reported rates for younger adults in their early twenties in Sweden (49%) 3 . This supports the notion that the frequency of pain increases rapidly during early adulthood and younger middle age in this population.…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence of pain in this study is similar to previous findings of pain in adults with CP in Sweden, 28 but higher than recently reported rates for younger adults in their early twenties in Sweden (49%). 3 This supports the notion that the frequency of pain increases rapidly during early adulthood and younger middle age in this population. The prevalence of pain (66.5%) was slightly lower than what has been reported internationally (70-82%), 1,2,9 but this may be partially explained by different inclusion and exclusion criteria, definitions of pain, and recall periods.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations